Role of Spinal Cord Akt-mTOR Signaling Pathways in Postoperative Hyperalgesia Induced by Plantar Incision in Mice - Xu, Bing; Liu, Su-Su; Wei, Jin; Jiao, Zi-Yin; Mo, Cheng; Lv, Cheng-Mei; Huang, Ai-Lan; Chen, Qi-Bo; Ma, Li; Guan, Xue-Hai (Frontiers in Neuroscience, 2020)
Poor postoperative pain (POP) control increases perioperative morbidity, prolongs hospitalization days, and causes chronic pain. However, the specific mechanism(s) underlying POP is unclear and the identification of optimal perioperative treatment remains elusive. Akt and mammalian target of rapamycin (mTOR) are expressed in the spinal cord, dorsal root ganglion, and sensory axons. In this study, we explored the role of Akt and mTOR in pain-related behaviors induced by plantar incision in mice. Plantar incision activated spinal Akt and mTOR in a dose-dependent manner. Pre-treatment with Akt inhibitors intrathecally prevented the activation of mTOR dose-dependently. In addition, blocking the Akt-mTOR signaling cascade attenuated pain-related behaviors and spinal Fos protein expression induced by plantar incision. Our observations demonstrate that Akt-mTOR might be a potential therapeutic target for the treatment of POP.